Composite current collector and preparation method thereof
By introducing metallized fibers into the matrix of the composite fluid collector, the conductive ability and ductility are improved, and the problems of poor conductivity and uneven deformation in the composite fluid collector are solved, which significantly improves the power performance and safety performance of the battery.
Patent Information
- Application Number
- CN202411805349.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The conductivity of the polymer layer in the composite liquid collecting fluid is poor, resulting in large internal resistance of the battery cell, limiting the power performance of the battery; at the same time, during the rolling process, the polymer layer deforms greatly, resulting in uneven extension of the material area and the foil area, affecting the processing of the electrode sheet.
Metalized fiber reinforced composite materials are used as the matrix for composite fluid collection. By covering the metal layer on the surface of the insulating fiber, the conductivity is improved, and by appropriately adjusting the aspect ratio of the fiber and the thickness of the metal layer, the ductility performance of the matrix is optimized to match the extension of the foil.
It significantly improves the conductivity of the composite fluid collection, reduces the internal resistance of the battery cell, reduces the charge and discharge temperature rise, improves the battery power performance and cycle life, and improves the compaction density and processing performance of the pole sheet.
Smart Images

Figure CN119650704A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite current collector and a preparation method thereof, belonging to the technical field of batteries. Background Art
[0002] The continuous improvement of the performance of electric vehicles and portable electronic products has urgently required the next generation of high energy density and high safety lithium-ion batteries. In order to improve the energy density of batteries, reducing the thickness and quality of current collectors has become the main trend of the current collector technology development. Composite current collectors have obvious advantages over traditional current collectors. The current composite current collector is usually a sandwich structure, with the middle layer being polymer materials such as PET (polyethylene terephthalate), PP (polypropylene), and PI (polyimide), and the outer layer being metal materials such as copper and aluminum. The middle layer of the composite current collector is plastic, which has a lower density than metal, and has obvious advantages in improving energy density. When the battery cell has thermal runaway, the polymer material melts quickly, suppressing the heat generation in the battery cell and improving safety performance. However, the composite current collector still has obvious disadvantages. First, the poor conductivity of the polymer layer will increase the internal resistance of the battery cell, resulting in a large temperature rise during the charge and discharge process, limiting the battery power performance; second, during the rolling process, when the compaction density of the pole piece is large, the polymer layer deforms greatly, resulting in excessive elongation of the pole piece in the material area, while the elongation of the foil area is smaller than that of the material area, resulting in uneven elongation of the material area and the foil area, resulting in bending of the pole piece, affecting subsequent processing. Therefore, it is necessary to increase the conductivity of the intermediate layer of the composite current collector and reduce its deformation rate during the rolling process to improve the comprehensive performance of the composite foil. Summary of the invention
[0003] To solve the above problems, the present invention provides a composite current collector that improves conductivity, reduces the internal resistance of the battery cell, and thus improves the phenomenon of large temperature rise during charging and discharging. By improving the intermediate matrix structure and composition, its ductility is matched with that of the foil, and the deformation of the electrode is suppressed, laying the foundation for industrial preparation.
[0004] An object of the present invention is to provide a composite current collector, the composite current collector comprising a first conductive layer, a second conductive layer and a substrate disposed between the first conductive layer and the second conductive layer.
[0005] The matrix includes a polymer material and metallized fibers dispersed in the polymer material, wherein the metallized fibers are insulating fibers coated with a metal layer on the surface, and the mass percentage of the insulating fibers in the matrix is not less than 10%, such as 10%, 10.5%, 11%, 11.5%, 12%, 15%, 18%, 18.5%, 19%, 19.5%, 20%, 30%, 40%, 50%, etc., including but not limited to the proportions listed above, and most preferably 10%-20%. Accordingly, the mass percentage of the polymer material in the matrix is not higher than 90%, such as 89.9%, 89.5%, 89%, 88%, 85%, 80%, 79.5%, 79%, 77%, 70%, 60%, 50%, etc., including but not limited to the proportions listed above, and most preferably 80%-90%.
[0006] Furthermore, in the metallized fiber, the aspect ratio of the insulating fiber is (50-500):(1-10), and most preferably (50-100):1.
[0007] Furthermore, in the metallized fibers, the insulating fiber can be selected from at least one of aramid fiber, aramid fiber, polyimide, etc. Aramid fiber is most preferred.
[0008] Furthermore, in the metallized fiber, the ratio of the diameter of the insulating fiber to the thickness of the metal layer is (10-100):(1-5), and most preferably is 25:1.
[0009] Furthermore, the metal in the metal layer may be any conductive metal, including but not limited to nickel, copper, aluminum, silver, gold, zinc, and the like.
[0010] Furthermore, the polymer material is plastic (especially thermoplastic resin). Preferably, the polymer material includes but is not limited to at least one of polyethylene terephthalate, polypropylene, polyethylene and polycarbonate.
[0011] Furthermore, the “dispersing” method includes but is not limited to pressing the insulating fibers whose surfaces are coated with molten polymer materials.
[0012] Furthermore, the thickness ratio of the first conductive layer, the substrate and the second conductive layer is (1-3): (4-20): (1-3).
[0013] Furthermore, the first conductive layer and the second conductive layer are made of metal, especially aluminum metal.
[0014] Furthermore, additives may be added to the matrix, and the mass percentage of additives in the matrix is 0.2%-1%.
[0015] Furthermore, the types of additives include but are not limited to antioxidants, conductive agents, flame retardants, and the like.
[0016] The present invention also provides a method for preparing a composite current collector, comprising the following steps:
[0017] S1, preparing an insulating fiber with a metal layer coated on the surface to obtain a metallized fiber;
[0018] S2, mixing the metallized fiber with a molten polymer material, pressing, and obtaining a matrix; the mass percentage of the metallized fiber in the matrix is not less than 10%;
[0019] S3, compounding the substrate with the first conductive layer and the second conductive layer so that the substrate is located between the first conductive layer and the second conductive layer to obtain the composite current collector.
[0020] Furthermore, any feasible method may be used to prepare the insulating fiber with a metal layer on the surface, including but not limited to chemical plating. For example, the steps of preparing the metallized fiber include: washing the insulating fiber with an organic solvent and water respectively, treating the insulating fiber with chlorine after drying, and chemically plating the insulating fiber with a solution containing a metal salt after the treatment to obtain the insulating fiber with a metal layer on the surface.
[0021] Furthermore, in step S2, the mixing includes preparing metallized fibers with molten polymer material coated on the surface by melt impregnation. Preferably, the metallized fibers are passed through heated polymer material to press the pulled material, the heating temperature is 130-200°C, and the heating time is 20-90s.
[0022] Another object of the present invention is to provide a pole piece, comprising a current collector and an active layer arranged on at least one side of the composite current collector along the thickness direction.
[0023] Furthermore, the electrode sheet may be a positive electrode sheet or a negative electrode sheet, and correspondingly, the active layer may be a positive electrode active layer or a negative electrode active layer.
[0024] Furthermore, the positive electrode active layer comprises a positive electrode active material, a conductive agent and a binder. The positive electrode active layer comprises the following components in mass percentage: 75-95% of the positive electrode active material, 5-15% of the conductive agent and 5-15% of the binder.
[0025] Furthermore, the negative electrode active layer comprises a negative electrode active material, a conductive agent and a binder. The negative electrode active layer comprises the following components in mass percentage: 75-95% of the negative electrode active material, 5-15% of the conductive agent and 5-15% of the binder.
[0026] Furthermore, the thickness of the composite current collector ranges from 6 to 26 μm, for example, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, etc., including but not limited to the thickness values listed above.
[0027] The embodiment of the present invention also provides a method for preparing the above-mentioned pole piece, comprising the following steps:
[0028] S01, preparing active slurry by mixing the positive electrode active material or the negative electrode active material, the conductive agent and the binder in the formulated amount;
[0029] S02, coating the active slurry on at least one side of the composite current collector along the thickness direction, drying to obtain an active layer, and pressing to obtain the pole piece.
[0030] The embodiments of the present invention also provide a battery comprising the pole piece.
[0031] Furthermore, the battery includes a lithium ion battery, a sodium ion battery, etc.
[0032] Beneficial effects of the present invention:
[0033] The present invention uses metallized fiber reinforced composite materials to partially replace traditional polymer materials as the composite current collector matrix. The metallized fiber uses insulating fiber as the base and is plated with a metal layer on the surface, which can greatly improve the conductivity, reduce the internal resistance of the battery cell and reduce the temperature rise of battery charging and discharging, improve the power performance and cycle life of the battery cell, and the polymer material can improve the energy density and can quickly melt when the battery cell has thermal runaway, inhibiting the short heat generation in the battery cell and thus improving the safety performance. The metallized fiber reinforced composite material is applied to the composite current collector, which greatly improves the strength of the matrix, so that the composite current collector can control the deformation rate under the greater pressure during the rolling process, reducing the difficulty of the later stage processing, thereby increasing the overall compaction density of the pole piece. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the structure of the composite current collector of the present invention. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0036] As described in the background technology, the middle layer of the existing sandwich structure composite current collector is a pure polymer material, which has poor electrochemical performance and safety. In order to improve the power performance and safety performance of the composite current collector, the present invention introduces a specially designed conductive material-metallized fiber. The metallized fiber is an insulating fiber with a metal layer deposited on the surface. It has been verified that the appropriate addition of the metallized fiber to the base material can improve the battery performance, and can effectively fuse during the process of needle puncture, thermal runaway, etc., thereby improving safety. At the same time, the background technology also points out that in the process of composite current collector processing, there is deformation caused by uneven extension of the material area and the foil area. The solution of the present invention can greatly reduce the difference in ductility of different regions, improve the deformation of the composite current collector during the pressing process, and thus improve the performance of the composite foil.
[0037] Specifically:
[0038] The present invention provides a composite current collector, comprising a first conductive layer, a second conductive layer and a substrate disposed between the first conductive layer and the second conductive layer.
[0039] The matrix includes a polymer material and metallized fibers dispersed in the polymer material, wherein the metallized fibers are insulating fibers coated with a metal layer on the surface, and the mass percentage of the metallized fibers in the matrix is not less than 10%, such as 10%, 10.5%, 11%, 11.5%, 12%, 15%, 18%, 18.5%, 19%, 19.5%, 20%, 30%, 40%, 50%, etc., including but not limited to the proportions listed above, and most preferably 10%-20%. Accordingly, the mass percentage of the polymer material in the matrix is not higher than 90%, such as 89.9%, 89.5%, 89%, 88%, 85%, 80%, 79.5%, 79%, 77%, 70%, 60%, 50%, etc., including but not limited to the proportions listed above, and most preferably 80%-90%. Polymer materials are conventional base materials for composite current collector matrix layers, and have advantages in improving energy density and safety, and are large-scale and low-cost. The present invention partially replaces the polymer materials in the matrix layer with metallized fibers, and introduces the advantages of metallized fibers while retaining the advantages of polymer materials. Targeted improvements can be made under the premise of controlling costs, including but not limited to improving electrical conductivity and improving ductility as needed.
[0040] Preferably, in the metallized fiber, the aspect ratio of the insulating fiber is (50-500): (1-10). The aspect ratio of the fiber has a significant effect on the performance of the reinforced composite material. The aspect ratio refers to the ratio of the length of the fiber to its diameter, which is directly related to the dispersion of the fiber in the matrix, the adhesion to the matrix, etc. An increase in the aspect ratio can improve the toughness and strength of the matrix. A too low aspect ratio cannot guarantee sufficient mechanical properties of the composite material, but after exceeding a certain range, the reinforcing effect of the fiber may no longer increase significantly, but instead increase the cost.
[0041] Preferably, in the metallized fiber, the insulating fiber can be selected from at least one of aromatic sulfone, aramid, polyimide, etc. Aromatic sulfone is most preferred, and aromatic sulfone has excellent strength, heat resistance, flame retardancy and chemical stability, which also make it more suitable for composite current collector materials. Since the foil is not squeezed and stretched during the rolling process of the composite current collector, and the large stretch of the material area causes the pole piece to bend, the present invention introduces insulating fibers with specific mechanical properties into the metallized fiber, which can improve the overall strength of the matrix layer, reduce the stretch of the material area, and make the material area and the foil area stretch evenly.
[0042] Preferably, in the metallized fiber, the ratio of the diameter of the insulating fiber to the thickness of the metal layer is (10-100): (1-5). For example, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, etc., including but not limited to the ratios listed above, and most preferably 25:1. The diameter of the fiber and the thickness of the metal layer on its surface will also have a certain effect on the mechanical properties of the composite material. The larger the diameter of the fiber, the more obvious the strength enhancement effect, and the interface area for bonding with the matrix is provided, which helps to improve the overall performance. However, too large a diameter may cause brittleness of the composite material and reduce its toughness. Moreover, the thickness of the metal layer is directly related to the migration path and resistivity of the electrons. The thicker the metal layer, the better the conductivity. The electrons have a longer path to transmit through the metal layer, which reduces the overall resistance, but an overly thick metal layer may also increase the resistance to electron transmission. Therefore, the ratio of the insulating fiber diameter to the thickness of the metal layer also affects the conductive properties of the composite current collector. Experimental verification has shown that the small diameter of the insulating fiber causes a significant reduction in its strength, the pole pieces of the composite current collector stretch too much during the rolling process, and the thickness of the metal layer on the surface of the insulating fiber is too thin, which has limited effect on improving the conductivity of the PSA, resulting in poor overall conductivity of the composite current collector and a significant increase in the internal resistance of the battery.
[0043] Preferably, the metal in the metal layer may be any conductive metal, including but not limited to nickel, copper, aluminum, silver, gold, zinc, etc.
[0044] In the present invention, the polymer material is plastic (especially thermoplastic resin). Preferably, the polymer material includes but is not limited to at least one of polyethylene terephthalate, polypropylene, polyethylene and polycarbonate.
[0045] Preferably, the "dispersion" method includes but is not limited to pressing the insulating fiber with the surface coated with molten polymer material. This method can control the thickness of the base layer, which is convenient for industrial production. In addition, it can squeeze out the air inside the material to make it denser. This is a processing method that can achieve both uniformity and the best combination of the two. The composite current collector obtained by dispersion in this way has better electrical properties and the effect of improving the deformation of the pole piece than other dispersion methods.
[0046] In the composite current collector of the present invention, the thickness ratio of the first conductive layer, the substrate, and the second conductive layer is (1-3): (4-20): (1-3), such as 1.5:5:1.5, 1.5:7:1.5, 1.5:10:1.5, 1.5:15:1.5, 1:5:1, 1:15:1, 3:5:3, 3:15:3, etc., including but not limited to the above-mentioned ratios. It is well known that the thickness of the conductive layer and the intermediate substrate layer directly affects the conductive properties of the current collector. In the present invention, it is preferred that the thickness of the intermediate substrate layer is 4-20 μm, and the thickness of the metal layer is 1-3 μm.
[0047] Preferably, in the first conductive layer and the second conductive layer, the first conductive layer and the second conductive layer are composed of metal, in particular, aluminum metal.
[0048] Preferably, additives may be added to the matrix, and their mass percentage in the matrix is 0.2%-1%, for example 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 0.95%, etc., including but not limited to the proportions listed above.
[0049] Preferably, the types of additives include but are not limited to antioxidants, conductive agents, flame retardants, etc. Among them, the conductive agent can increase the conductivity of the matrix and improve the overall electronic conduction of the foil. The appropriate addition of the conductive agent can improve the electrical properties of the composite current collector. Preferably, the mass percentage in the matrix is 0.2%-0.8%. Antioxidants can effectively prevent the thermal oxidation degradation of polymer materials during long-term aging. They are also a highly efficient processing stabilizer that can improve the discoloration resistance of polymer materials under high-temperature processing conditions. Flame retardants can inhibit the combustion of the matrix at high temperatures and inhibit thermal runaway of the battery cell.
[0050] The present invention also provides a method for preparing a composite current collector, comprising the following steps:
[0051] S1, preparing an insulating fiber with a metal layer coated on the surface to obtain a metallized fiber;
[0052] S2, mixing the metallized fiber with a molten polymer material, pressing, and obtaining a matrix; the mass percentage of the metallized fiber in the matrix is not less than 10%;
[0053] S3, compounding the substrate with the first conductive layer and the second conductive layer so that the substrate is located between the first conductive layer and the second conductive layer to obtain the composite current collector.
[0054] Preferably, the insulating fiber with the metal layer coated on the surface can be prepared by any feasible method, including but not limited to chemical plating. In one embodiment of the present invention, the metal layer is prepared by chemical plating, and a metal coating layer of a certain thickness can be obtained, and the coating thickness is uniform. For example, the steps of preparing the metallized fiber include: washing the insulating fiber with an organic solvent and water respectively, drying and then subjecting the insulating fiber to chlorine treatment, and after the treatment, chemically plating the insulating fiber with a solution containing a metal salt to obtain the insulating fiber with the metal layer coated on the surface.
[0055] Preferably, in step S2, the mixing includes preparing metallized fibers with molten polymer material coated on the surface by melt impregnation. Preferably, the metallized fibers are passed through the heated polymer material so that the molten polymer material is evenly impregnated on the surface of the metallized fibers, thereby achieving uniform dispersion of the fibers in the polymer material during subsequent pressing.
[0056] Preferably, in step S2, preparing a molten polymer material includes the step of heating the polymer material. The heating temperature is 130-200°C, such as 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 199°C, etc.; the heating time is 20-90s, such as 25s, 30s, 35s, 40s, 45s, 50s, 55s, 60s, 65s, 70s, 75s, 80s, 85s, 89s, etc. The viscosity of polymer materials such as thermoplastic resins is greatly affected by temperature. As the temperature increases, the viscosity of the resin decreases and the fluidity increases, which helps the resin to better impregnate the fiber and improve the impregnation effect. At the same time, temperature control is also crucial for the interface bonding between resin and fiber. Within this temperature range, the bonding between resin and fiber can be promoted, thereby improving the overall performance of the composite material. The heating time affects the melt index and viscosity of the thermoplastic resin, which will also affect the impregnation effect of the resin on the fiber.
[0057] Of course, the present invention adopts the method of pulling the metallized fiber into the mold to fully impregnate it with the molten resin material and then pulling it out. It is also necessary to find a balance between process conditions such as the pulling rate and the impregnation temperature. Although an increase in the pulling rate can increase the output, a too fast pulling rate may make it difficult for the molten polymer material to completely impregnate the fiber. Technical personnel in this field can make adjustments as needed.
[0058] Preferably, the composite current collector of the present invention comprises an intermediate substrate layer and a metal conductive layer, wherein the metal conductive layers are disposed on both sides of the intermediate substrate layer:
[0059] The middle base layer is a metallized fiber reinforced composite material, which uses thermoplastic resin as the matrix and metallized fiber as the reinforcement material. The thermoplastic resin can be one or more materials of PET, PP, PE (polyethylene), PC (polycarbonate), the thermoplastic resin accounts for 80-90% of the middle base layer, the metallized fiber accounts for 10-20% of the middle base layer, the metallized fiber uses PSA fiber as the base, and the surface is plated with metal; the thickness of the middle base layer is 4-20μm, the fiber diameter is 0.2-2μm, and the coating thickness is 10-100nm.
[0060] The metal conductive layer is one or more materials selected from copper, aluminum, and nickel, and the thickness of the metal conductive layer is 1-3 μm.
[0061] Preferably, the thickness of the composite current collector is in the range of 6-26 μm, for example 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, etc., including but not limited to the thickness values listed above.
[0062] Preferably, the steps of preparing the composite current collector are as follows:
[0063] (1) The PSA fiber is ultrasonically cleaned in any solvent such as acetone, ethanol, cyclohexane, chlorobenzene, etc. for 20-60 minutes, washed with pure water and dried, and then the PSA fiber is immersed in a sodium chloride-hydrochloric acid or potassium chloride-hydrochloric acid solution with a pH value of 3-5 for 15-30 minutes for chlorine treatment, and then fully washed with pure water to remove acidic substances; this treatment can achieve surface cleaning (removal of oil, impurities, oxide layer, etc.), increase surface active sites, improve surface wetting, regulate surface roughness, etc., thereby improving chemical plating uniformity and adhesion.
[0064] (2) The washed PSA is immersed in a 4-6 g / L AgNO3 or CH3COOAg solution at 60-75°C for 20-40 min, and then washed with pure water. Subsequently, it is immersed in a 2-3 g / L NaBH4 or KBH4 aqueous solution and allowed to stand at room temperature for 10-20 min before being washed with pure water.
[0065] (3) preparing a chemical plating solution, wherein nickel acetate or nitrate is used as nickel salt, with a concentration of 5-15 g / L; one or more of sodium citrate, tartaric acid, and ethylenediaminetetraacetic acid is used as a complexing agent, with a concentration of 4-8 g / L; one or more of dimethylamine borane, sodium aminophenol sulfate, sodium hypophosphite, and sodium nitrite is used as a reducing agent, with a concentration of 0.5-1 g / L; and ammonia water is added to adjust the pH value to 8-9.
[0066] (4) The PSA fiber is placed in a chemical plating solution at 60-70° C. for 20-60 minutes, then washed with pure water and dried to obtain a metallized fiber, which is then dried in a drying oven at 70-85° C. for 0.5-2 hours.
[0067] (5) The thermoplastic resin material is placed in a vacuum environment at 130-200° C. for 2-10 hours and then added to a high-speed disperser. Additives are then added and mixed for 0.5-2 hours, and the molten material is extruded into a mold.
[0068] (6) The metallized fiber is pulled into the mold, fully infiltrated with the molten resin material, and then pulled out, and the metallized fiber reinforced composite material is obtained after roll forming by a roller press. The mold temperature is maintained at 130-200°C, and the roll thickness is controlled to be 4-20 μm.
[0069] (7) Preparation of composite current collector: One or more metals such as aluminum, copper, nickel, etc. are plated on the surfaces of both sides of the substrate layer by magnetron sputtering or vacuum evaporation to form a conductive layer to complete the preparation of the current collector.
[0070] The present invention also provides a pole piece, comprising a current collector and an active layer arranged on at least one side of the composite current collector along the thickness direction.
[0071] Preferably, the electrode sheet may be a positive electrode sheet or a negative electrode sheet, and correspondingly, the active layer may be a positive electrode active layer or a negative electrode active layer.
[0072] Preferably, the positive electrode active layer comprises a positive electrode active material, a conductive agent and a binder. The positive electrode active layer comprises the following components by mass percentage: 75-95% of the positive electrode active material, 5-15% of the conductive agent and 5-15% of the binder.
[0073] Preferably, the negative electrode active layer comprises a negative electrode active material, a conductive agent and a binder. The negative electrode active layer comprises the following components in mass percentage: 75-95% of the negative electrode active material, 5-15% of the conductive agent and 5-15% of the binder.
[0074] Preferably, the positive electrode active material and the negative electrode active material used in the present invention can be any material commonly used in the field of battery technology, and the conductive agent used in the present invention is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.
[0075] Preferably, the binder is a binder well known to those skilled in the art, without any particular limitation, such as chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacryloyl, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymer and guar gum copolymer. In the embodiment of the present invention, PVDF is selected.
[0076] Preferably, the thickness of the positive electrode active layer or the negative electrode active layer is in the range of 100-300 μm, for example, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, etc., including but not limited to the thickness values listed above.
[0077] The embodiment of the present invention also provides a method for preparing the above-mentioned pole piece, comprising the following steps:
[0078] S01, preparing active slurry by mixing the positive electrode active material or the negative electrode active material, the conductive agent and the binder in the formulated amount;
[0079] S02, coating the active slurry on at least one side of the composite current collector along the thickness direction, drying to obtain an active layer, and pressing to obtain the pole piece.
[0080] The embodiments of the present invention also provide a battery (such as a lithium-ion battery, a sodium-ion battery, etc.) containing the pole piece.
[0081] Example 1
[0082] A composite current collector, comprising an intermediate substrate layer and a metal conductive layer, wherein the metal conductive layers are disposed on both sides of the intermediate substrate layer:
[0083] The middle base layer is composed of thermoplastic resin polyethylene terephthalate (PET), antioxidant 1010 and metallized fiber. By mass percentage, PET accounts for 80%, antioxidant 1010 accounts for 1%, and metallized fiber accounts for 19%; wherein, the thickness of the middle base layer is 5 μm, and the metallized fiber contains PSA fiber (polystyrene sulfone) and a surface nickel layer. The diameter of the PSA fiber is 0.5 μm, the aspect ratio is 50:1, and the thickness of the surface nickel layer is 20 nm.
[0084] The metal conductive layer is aluminum, with a total thickness of 3 μm.
[0085] The preparation method of the composite current collector is as follows:
[0086] S1. PSA fibers with an average diameter of 0.5 μm were ultrasonically cleaned in acetone for 30 minutes, washed with pure water and dried, and then the PSA fibers were immersed in a sodium chloride-hydrochloric acid solution with a pH value of 4 for 20 minutes for chlorine treatment, and then fully washed with pure water to remove acidic substances.
[0087] S2. Soak the washed PSA fiber in a 5 g / L AgNO3 solution at 75°C for 30 min, then wash it with pure water. Subsequently, soak it in a 2.5 g / L NaBH4 aqueous solution, let it stand at room temperature for 15 min, and then wash it with pure water.
[0088] S3. Prepare a chemical plating solution, wherein nickel acetate is used as the nickel salt, and the concentration is 10 g / L; sodium citrate is used as the complexing agent, and the concentration is 6 g / L; dimethylamine borane is used as the reducing agent, and the concentration is 0.5 g / L; and ammonia water is added to adjust the pH value to 8.
[0089] S4. Place the PSA fiber obtained in S2 in a chemical plating solution at 65°C for 30 minutes, then wash with pure water and dry to obtain a metallized fiber, and dry in a drying oven at 80°C for 1 hour.
[0090] S5. Place the PET in a vacuum environment at 130-200°C for 2-10 hours and then add it to a high-speed disperser. Then add an antioxidant and mix for 0.5-2 hours. Extrude the molten resin material into a mold.
[0091] S6, pulling the metallized fiber into the mold, fully soaking it with the molten resin material and pulling it out, and rolling it through a roller press to obtain the middle base layer. The mold temperature is maintained at 165°C, and the rolling thickness is controlled to be 5μm.
[0092] S7. Preparation of composite current collector: 1.5 μm aluminum metal is plated on both sides of the intermediate substrate layer by magnetron sputtering or vacuum evaporation to form a metal conductive layer to complete the preparation of the current collector.
[0093] Example 2
[0094] The proportion of PET in the middle base layer is controlled to be 89.8%, the proportion of antioxidant 1010 is controlled to be 0.2%, and the proportion of metallized fiber is controlled to be 10%. The remaining operations are the same as those in Example 1.
[0095] Example 3
[0096] The diameter of the PSA fiber was adjusted to 0.2 μm, and the remaining operations were the same as in Example 1.
[0097] Example 4
[0098] The diameter of the PSA fiber was adjusted to 2 μm, and the remaining operations were the same as in Example 1.
[0099] Example 5
[0100] The thickness of the nickel layer on the surface of the PSA fiber was adjusted to 50 nm, and the remaining operations were the same as in Example 1.
[0101] Example 6
[0102] The PSA fiber was replaced by PI (polyimide) fiber, and the remaining operations were the same as in Example 1.
[0103] Example 7
[0104] The surface nickel layer is replaced by an aluminum layer, and the thickness of the surface aluminum layer is controlled to be 10 nm. The aspect ratio of the PSA fiber is 500:1. The remaining operations are the same as in Example 1.
[0105] Example 8
[0106] PET was replaced by PP, the thickness of the middle base layer was controlled to be 15 μm, and the rest of the operations were the same as in Example 1.
[0107] Example 9
[0108] The proportion of the antioxidant 1010 in the middle base layer is controlled to be 0.5%, and then 0.5% of the conductive agent (carbon black) is added. The rest of the operations are the same as in Example 1.
[0109] Example 10
[0110] The middle base layer was replaced with a non-woven fabric prepared by blending PET fiber and metallized fiber, and the remaining operations were the same as in Example 1.
[0111] Comparative Example 1
[0112] The metallized fibers were removed, and the middle substrate layer contained 5 μm pure PET. The remaining operations were the same as in Example 1.
[0113] Comparative Example 2
[0114] The nickel nanoparticles are mixed with the molten resin material to prepare an intermediate substrate layer, and the remaining operations are the same as in Example 1.
[0115] Comparative Example 3
[0116] The PSA fiber was replaced with carbon fiber, and the remaining operations were the same as in Example 1.
[0117] Comparative Example 4
[0118] The proportion of PET in the middle base layer is controlled to be 94.8%, the proportion of antioxidant 1010 is controlled to be 0.2%, and the proportion of metallized fiber is controlled to be 5%. The remaining operations are the same as those in Example 1.
[0119] Test Case
[0120] The test process and results are as follows:
[0121] The composite current collector prepared in the embodiment and the comparative example was used as the positive electrode current collector of the lithium ion battery, and 230 g / m 2 The positive electrode slurry (the active material in the positive electrode slurry is nickel cobalt lithium manganese oxide) is rolled to a thickness of 155 μm. Before rolling, the length of 100 mm is marked between the material area and the edge of the foil. After rolling, the length of the marked area L is measured. The elongation rate = (L-100) / 100. The smaller the value, the better the foil processing performance.
[0122] After the rolled pole pieces are assembled into batteries with the same negative electrode (artificial graphite), separator (polypropylene separator with a thickness of 12 μm), electrolyte (LiPF6 dissolved in a solvent of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate with a ratio of 1:1:1, and a concentration of 1.2 mol / L), and shell, the batteries are discharged at 50% SOC at 2C for 30S to measure DCR (direct current resistance). The smaller the value, the better the conductivity of the foil.
[0123] After the battery is fully charged, discharge it at 3C until the cut-off voltage, and record the discharge capacity retention rate and temperature rise. The specific test process is as follows:
[0124] 1. Stand at 25℃ for 30min;
[0125] 2. 0.33C constant current and constant voltage charging to 4.25V, cut-off current 0.05C;
[0126] 3. Let stand for 30 minutes;
[0127] 4. 1C constant current discharge to 2.5V is recorded as C1;
[0128] 5. Let stand for 30 minutes;
[0129] 6. 0.33C constant current and constant voltage charging to 4.25V, cut-off current 0.05C;
[0130] 7. Let stand for 30 minutes;
[0131] 8. Discharge at 3C constant current to 2.5V and record it as C2.
[0132] 3C discharge capacity retention rate = C2 / C1, 3C discharge temperature rise is the temperature difference before and after 3C discharge in step 8.
[0133] The battery cell is subjected to a needle puncture test to evaluate the safety performance of the foil. The test process is as follows: a high-temperature resistant steel needle (tungsten steel needle) with a diameter of 1 mm is used to puncture the battery cell at a speed of 3 mm / s from a direction perpendicular to the large surface of the fully charged battery cell to ensure that the steel needle penetrates the battery cell. The test is maintained for 60 minutes. The battery cell passes the test if no open flame occurs.
[0134] The test results are shown in Table 1.
[0135] Table 1
[0136]
[0137]
[0138] From the test results, it can be seen that the composite current collector used in the embodiment has obvious advantages over the ordinary composite current collector used in comparative example 1. The introduction of high-strength metallized fibers inhibits its deformation during the rolling process, and the elongation of the pole piece is reduced from 1.22% to 0.38%; and from the DCR results, it can be seen that the current collector used in the embodiment has a better effect in reducing the internal resistance, and when the battery cell is discharged at a high rate, the capacity retention rate is higher and the temperature rise is lower, which further proves that the introduction of high-conductivity metallized fibers reduces the overall resistance of the composite current collector. In Example 2, reducing the content of metallized fibers has a slight effect on the performance, and in Comparative Example 4, after reducing the content of metallized fibers to 5%, the elongation, DCR, discharge temperature rise and other properties are significantly reduced. In Examples 3-9, the diameter of the insulating fiber PSA, the thickness of the surface nickel layer, the type of insulating fiber, the type of polymer material, the type of surface metal layer, etc. are adjusted within a certain range, and the performance of the prepared composite current collector is relatively excellent. Of course, in actual operation, a certain amount of conductive agent can be added as needed to further improve its electrical properties. However, when the molten polymer material is replaced by a fibrous polymer material for the dispersion of the metallized fiber, its performance is reduced. In Comparative Example 2, the conductive nanoparticles are directly mixed with PET. Although the electrochemical performance of the current collector is improved to a certain extent compared with the pure polymer material, the overall effect is not as good as the embodiment. More importantly, directly mixing the particles cannot improve the defect that the foil and the material area cannot be evenly extended. In Comparative Example 3, the insulating fiber PSA is replaced with a conductive fiber, but unexpectedly, the electrochemical performance of the composite current collector is not further improved, but has a significant decline. This may be because the base layer of the fully conductive material cannot be effectively melted to break the positive and negative electrodes during the process of needle puncture and thermal runaway, thereby failing to effectively exert the advantages of the composite current collector. In Comparative Example 4, the proportion of metallized fibers in the middle base layer is too low, and a small amount of metallized fibers has no obvious effect on improving the strength and conductivity of the composite current collector, resulting in excessive rolling extension of the pole piece and a large internal resistance of the battery cell.
[0139] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a composite current collector, characterized in that: The following steps are involved: S1, preparing an insulating fiber with a metal layer coated on the surface to obtain a metallized fiber; S2, mixing the metallized fiber with a molten polymer material, pressing, and obtaining a matrix; the mass percentage of the metallized fiber in the matrix is not less than 10%; S3. Composite the substrate with the first conductive layer and the second conductive layer so that the substrate is located between the first conductive layer and the second conductive layer to obtain the composite current collector.
2. The preparation method according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) The mass percentage of the metallized fibers in the matrix is 10%-20%; the mass percentage of the polymer material in the matrix is 80%-90%; (2) The first conductive layer and the second conductive layer are made of metal, (3) The polymer material is plastic; (4) The insulating fiber includes at least one of aramid fiber, aramid fiber and polyimide; (5) The material of the metal layer includes at least one of nickel, copper, aluminum, silver, gold, and zinc.
3. The preparation method according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) The thickness ratio of the first conductive layer, the substrate, and the second conductive layer is (1-3): (4-20): (1-3); (2) The aspect ratio of the insulating fiber is (50-500): (1-10); (3) The ratio of the diameter of the insulating fiber to the thickness of the metal layer is (10-100): (1-5).
4. The preparation method according to claim 1, characterized in that: In step S2, the mixing includes preparing metallized fibers with surfaces coated with molten polymer materials by melt impregnation; the melt impregnation method includes the step of passing the metallized fibers through heated polymer materials.
5. The preparation method according to claim 1, characterized in that: The preparation of the molten polymer material comprises the steps of heating the polymer material; the heating temperature is 130-200° C.; and the heating time is 20-90 seconds.
6. The preparation method according to claim 1, characterized in that: The steps of preparing metallized fiber include: washing the insulating fiber with organic solvent and water respectively, treating with chlorine after drying, and chemically plating the insulating fiber with a solution containing metal salt to obtain insulating fiber with a metal layer coated on the surface.
7. The preparation method according to claim 1, characterized in that: The mixing described in step S2 further includes the step of mixing with an additive; the additive comprises at least one of the following characteristics: (1) The mass percentage of the additive in the matrix is 0.2%-1%; (2) The additive includes at least one of an antioxidant, a conductive agent, and a flame retardant.
8. A composite current collector, characterized in that: The composite current collector includes a first conductive layer, a second conductive layer and a substrate disposed between the first conductive layer and the second conductive layer. The first conductive layer and the second conductive layer are made of metal. The matrix includes a polymer material and metallized fibers dispersed in the polymer material. The metallized fibers are insulating fibers with a metal layer coated on the surface. The mass percentage of the metallized fibers in the matrix is not less than 10%. The polymer material is plastic.
9. A pole piece, characterized in that: The pole piece comprises a composite current collector prepared by the preparation method according to any one of claims 1 to 7 or the composite current collector according to claim 8, and an active layer arranged on at least one side of the composite current collector along the thickness direction.
10. A battery, characterized in that: The battery comprises the electrode sheet according to claim 9.
Citation Information
Patent Citations
Flexible current collector, electrode containing flexible current collector, and battery
CN106898729A
Long-life lithium metal negative electrode and preparation method thereof
CN118610386A
Current collector for bipolar secondary battery
JP2010092607A
Current collector for secondary battery and electrode using same
WO2014208997A1
Composite current collector and preparation method therefor, electrode plate, battery, and electronic device
WO2024000802A1